KAJIAN PERUBAHAN PENGGUNAAN LAHAN DAN HARGA LAHAN DI WILAYAH SEKITAR PINTU TOL UNGARAN - Dinda Kholivia Masykuroh; Iwan Rudiarto (Diponegoro University, 2016)
The operation of section I of Semarang-Solo toll road provides alternative access to Semarang City from its hinterland, especially Ungaran Subdistrict. Improved accessibility from Semarang City to Ungaran has impacted to land use of the surrounding area. It can be seen from the increase in new built-up areas in Kalirejo as well as Sidomulyo Villages. The land use change also gives impact to land rents or prices. This study aims to assess the land use and land price changes in the Villages of Kalirejo and Sidomulyo as a result of the existence of the Ungaran toll-gate. The methods used are quantitative completed with observation and review of the relevant documents. This study uses spatial modeling approach with ArcGIS software. Spatial analysis is used to determine the change of land use that occurred in the two villages in 2003, 2011 and 2014. The results of this study show that the existence of the Ungaran toll gate has triggered changes of non-built-up into the built-up area. Changes have also been there in the price of land in the two villages. Besides, this dynamic situation has encouraged the emergence of new sub-center located in the Kalirejo Village.